Analysis of the Determinants of Extreme Poverty in North Morowali Regency - Monduu, Elisabet; Suparman, Suparman; Sading, Yunus; Rahman, Failur; Yohan, Yohan (Transpublika Publisher, 2025)
This study aims to empirically analyse the socio-economic determinants that influence the level of extreme poverty in North Morowali Regency. The main focus of this study lies on three independent variables, namely average length of schooling, life expectancy, and percentage of poor population. Using a quantitative approach, descriptive and verifiable methods were applied to secondary data from 2020–2023 obtained from the Central Statistics Agency (BPS) and related institutions. The analysis was conducted using multiple linear regression accompanied by classical assumption tests and significance testing. The results indicate that all three independent variables significantly influence extreme poverty, with a coefficient of determination (R²) of 0.794. Partially, average years of schooling and life expectancy have a positive and significant effect on reducing extreme poverty, while the percentage of the poor population has a negative and significant effect. These findings indicate that improving the quality of education and health is key to reducing extreme poverty, while high levels of general poverty exacerbate extreme poverty. The implication of this study is the importance of evidence-based regional policy formulation that focuses on comprehensive human development. The originality of this research lies in its approach, which integrates human development indicators into a model for measuring extreme poverty at the district level specifically.